2008
DOI: 10.1363/4016208
|View full text |Cite
|
Sign up to set email alerts
|

Implementing an Advance Emergency Contraception Policy: What Happens in the Real World?

Abstract: Strategies that may facilitate advance provision of emergency contraception include emphasizing the need for staff to offer it during all patient visits, providing patient-friendly information and streamlining clinic procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 19 publications
1
14
0
Order By: Relevance
“…Many women have incomplete knowledge surrounding EC, particularly related to timing, effectiveness, and side effects [8,9,12,13], despite its availability OTC for more than 2 years at the time of this study. Healthcare providers are not consistently providing information, although women view them as reliable sources of information [8,[13][14][15].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many women have incomplete knowledge surrounding EC, particularly related to timing, effectiveness, and side effects [8,9,12,13], despite its availability OTC for more than 2 years at the time of this study. Healthcare providers are not consistently providing information, although women view them as reliable sources of information [8,[13][14][15].…”
Section: Discussionmentioning
confidence: 99%
“…It is important to clarify that OTC EC, prior to 2013, was actually kept behind the counter, requiring individuals to go to the pharmacy counter, request the medication, and show proof of age. Many women perceive this requirement as an obstacle [8,9]. Cost is also a potential barrier to the use of EC ($10-$70) [10].…”
Section: Introductionintroductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2001, of those women reporting an unintended pregnancy, 52% claimed they were not using any contraceptive method at the time of conception (Burkman et al, 2006). In a study conducted in family health clinics, 43% of sexually active patients, mean age 23, reported not using birth control at least once in the previous month (Whittaker, Armstrong, & Adams, 2008). According to the National Survey of Family Growth in 2002, women overall reported using some form of contraception at least once in their lifetime, but remarkably only 31.5% of 15‐ to 19‐year‐olds and 60.7% of 20‐ to 24‐year‐olds reported using some form of contraception at the time of interview (CDC, 2005).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Existing study findings often describe attitudes, perceptions, and knowledge with some overlap. Nearly all studies indicate women's lack of knowledge as well as misconceptions about EC (Corbett et al, 2006; Cunnane et al, 2006; KFF, 2005; Whittaker et al, 2008). Corbett et al and Cunnane et al also reported a small percentage of women in their studies having religious or moral objections to EC.…”
Section: Emergency Contraceptionmentioning
confidence: 99%